1988
DOI: 10.1152/ajpendo.1988.254.6.e749
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical organ-specific adaptations to streptozotocin diabetes mellitus in adult rats

Abstract: Adult male Fisher rats injected with streptozotocin (Stz) to produce diabetes mellitus demonstrated a significant loss of total body weight associated with adipose and muscle tissue wasting. Paradoxically, intestinal mass and length were increased in Stz-treated rats despite catabolism of other tissues. Concomitant with increased intestinal mass, food and water intake increased significantly in Stz-diabetic animals. Renal weight was not reduced despite the fall in total body weight. It is proposed that the adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…According to the Law of Laplace, the wall tension is increased proportionally to the diameter, which explains why the intestine will rupture outside the anastomotic line after 5 days of healing [20]. The intestine in diabetic rats is increased in length, weight and surface area [13,14]. This corresponds with the increased weight and circumference we found in the present study.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…According to the Law of Laplace, the wall tension is increased proportionally to the diameter, which explains why the intestine will rupture outside the anastomotic line after 5 days of healing [20]. The intestine in diabetic rats is increased in length, weight and surface area [13,14]. This corresponds with the increased weight and circumference we found in the present study.…”
Section: Discussionsupporting
confidence: 76%
“…Contrary to most other organs and tissues in the diabetic rat, the intestinal tract is characterized by extensive growth in both weight and length [14]. Our study showed a marked increase in both circumference and DDW of the colon in the diabetic groups.…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…Hypertrophy of the small intestine musculature occurs in rats fed a diet rich in pectin (Brown et al 1979). Enlargement of the caecum is also observed in animals reared in germfree conditions (Philipps et al 1959;FaIk 1960), in relation to the absence of intestinal flora (Gordon 1959), and in diabetic animals (Pillion et al 1988). The histology of the caecal musculature has not yet been studied, but we have observed that in rats fed with a high-fibre diet, or born and bred in germ-free conditions, or affected by streptozotocin diabetes, the enlargement of the caecum is accompanied by a moderate thickening of its wall and thus involves a process of hypertrophy.…”
Section: Experimental Models In Laboratory Animalsmentioning
confidence: 98%
“…Overall growth, as measured by carcass weight and skeletal size parameters, was impaired. How ever, internal organs were relatively spared, except for the kidney, as was noted in pre vious studies [3,8], There is controversy in the literature about whether this is an effect o f the drug per se [17][18][19], The majority o f the discrepancy in weight between the STZtreated and control fetuses was accounted for by the differences in carcass weight.…”
Section: Discussionmentioning
confidence: 91%